Relation between morphologic development of the oral language and writing yield in students who attend fifth and sixth primary degree of in schools deprived pubilc and of socioeconomic level under Lima Metropolitan - Dioses Chocano, Alejandro (2004)
OBJECTIVE: To explore the relation between the morphologic development of the oral language and the yield in writing, students of the third cycle of primary assistants to schools of Metropolitan socioeconomic level under Lima. DESIGN: Cross sectional Correlational, made in 372 students of 5to and 6to degree, pertaining to schools Metropolitan public and deprived of Lima of low socioeconomic level, whose ages fluctuated between the 9 and 14 years. MATERIAL AN D METHODS: Descriptive study, the obtaining of the sample was by means of the deliberate Nested sampling. For the harvesting of the data the Adaptation of the Battery of the Language Objective and Criterial was used; and the Test of Production of the Written Text. RESUL TS: They confirmed this relation, although with a low level of association, which raises the necessity to incorporate new components for the analysis. CONCLUSIONS: The morphologic development of the oral language is related of direct and significant way to the writing yield, although to degree under association.